A Rare Case of Adult Aortopulmonary Window Combined with Anomalous Origin of the Right Pulmonary Artery from the Aorta Leading to Eisenmenger Syndrome. Issue 1 (January 2021) - Cui, Mingyue; Xia, Binfeng; Wang, Heru; Liu, Haihui; Yin, Xia
Aortopulmonary window is a rare congenital heart disease that can increase pulmonary vascular resistance, exacerbate left-to-right shunt and lead to heart failure and respiratory tract infections. Most patients die during childhood. We report a 53-year-old male patient with a large aortopulmonary window combined with anomalous origin of the right pulmonary artery from the aorta, with Eisenmenger syndrome and without surgery.